Can cognitive biases be good for entrepreneurs?. Issue 4 (10th April 2020) - Zhang, Haili; Bij, Hans van der; Song, Michael
Abstract : Purpose: While some studies have found that cognitive biases are detrimental to entrepreneurial performance, others have conjectured that cognitive biases may stimulate entrepreneurial action. This study uses a typology of availability and representative heuristics to examine how two patterns of biases affect entrepreneurial performance. Drawing on ideas from cognitive science, this study predicts that various levels of biases in each pattern stimulate entrepreneurial behavior and performance. Design/methodology/approach: A profile-deviation approach was employed to analyze data from 253 entrepreneurs and zero-truncated Poisson regression and the zero-truncated negative binomial regression to test hypotheses. Findings: This study finds some positive associations between a particular level of cognitive biases in each of the two patterns and entrepreneurial behavior and performance. Results show that the patterns of biases often stimulate and never hurt entrepreneurial behavior and performance. The opposite holds for a lack of cognitive biases, which hurts and never stimulates entrepreneurial behavior and performance. Originality/value: This study examines patterns of cognitive biases of entrepreneurs instead of single biases. The study broadens the perspective on the heuristics and cognitive biases of entrepreneurs by examining patterns of biases emanating from the availability and the representativeness heuristic that make a difference for entrepreneurial behavior and performance. The study also brings the "great rationality debate" closer to the entrepreneurship field by showing that a normative rule based on statistics and probability theory does not benefit entrepreneurial behavior and performance.